(untitled) (Journal of Pedagogical Inventions and Practices, 2021)
In this article, we will discuss ideas for easy English grammar learning, the implementation of English vocabulary, in particular through actions in teaching verbs, Listening Comprehension, and the usefulness of mobile applications that teach English.